The United States Constitution - Leebrick, Kristal, 1958- (Minnesota : Capstone Publishing, 2002)
Discusses how and why the United States Constitution was created; includes the difficulties with ratification by the states; and explains the Bill of Rights.
Includes bibliographical references (p. 45) and index.
Keywords: Constitutional history -- United States -- Juvenile literature; Constitutional history